Non Verbal Communication for Analyzing the Malpractice in Examinations– An Overview - T, Kujani; T, Sathya; R, Bhuvanya; S, Uma (International Journal of Engineering and Technology, 2018)
Nonverbal communication can specify the psychosomatic behavior of people involved in interpersonal communication. Many researchers have specified the importance of gesture intimation. In the paper, we shall apply the previously used computer vision hardware and Machine Learning techniques for capturing the postures students undergoing examination in the classroom atmosphere. The mainÂ Â Â Â Â Â intention is to classify the people who involved in misbehavior such as copying, prompting answers, sharing the answer scripts and any other such practices. Current situation prevailing is though a physical monitor, invigilator is available in the exam hall the students Â Â Â Â attempt to misbehave in various ways mentioned above. We discuss about the techniques to be employed to get an analysis of the Â Â Â Â Â Â behavior of each student involved in exam.Â